Fictions of youth : Pier Paolo Pasolini, adolescence, fascisms - Bondavalli, Simona, 1969- (Toronto Italian studies., 2015)
Fictions of Youth is a comprehensive examination of adolescence as an aesthetic, sociological, and ideological category in Pier Paolo Pasolini's prose, poetry, and cinema.